Analisis Prosedur Purchasing di SBY Residence - Ningsih, Pingit Kusuma; Ratnawati, Dyah (VISA: Journal of Vision and Ideas, 2024)
This writing aims to determine the effective and efficient implementation of the product purchasing process at SBY Residence. The method used is a qualitative method. Using primary data sources from SBY Residence. The purchasing accounting system is part of a company's accounting system that specifically manages and records purchase transactions for goods or services from suppliers. This system is important for controlling and tracking all aspects related to purchasing in order to support efficient business operations and fulfill financial planning and reporting needs. A hotel is a business that provides lodging services, food and drink providers, as well as other service facilities, all of whose services are intended for the general public, which is managed on a commercial basis. Within the hotel there are departments that manage it, one of which is the accounting department which is responsible for managing the hotel's finances and assets, including income, expenses, payments, storage of goods/assets, and cost control. Purchasing is a part of the accounting department which has a very dominant task in implementing purchasing processes and procedures. The results of this research are that the purchasing procedures carried out at SBY Residence according to standard operational procedures are not effective and efficient due to a lack of human resources which results in several jobs such as cost control and receiving being handled by the purchasing department.